PARTISIPASI SEMU PEREMPUAN MISKIN DALAM PROGRAM PEMBERDAYAAN MASYARAKAT - Ikhsan Muharma Putra (Universitas Islam Negeri Imam Bonjol Padang, 2015)
The background of this study is the lack of active participation of the poor women in the community empowerment program. This participation is especially on empowerment program promoted by the National Program for Community Empowerment in Rural Areas. Social development calls for changes in community conditions towards independence. His true empowerment program aimed at building communities, especially the poor women to be able to develop networking capabilities and capital in order to improve their welfare. This study used qualitative method and descriptive analysis. This study shows that community participation in the national community empowerment program is still apparent. These results conclude that there is a dominanation of certain groups in the decision-making in the participatory development process. As the result, poor women’s participation turned out to be false.